Efficiency of “Neo inulin” in the complex treatment of patients with type 2 diabetes - E. V. Katamanova; P. V. Kazakova; I. V. Kudaeva; A. N. Kuks; O. V. Ushakova (Acta Biomedica Scientifica, 2021)
Diabetes mellitus is one of the most serious medical, social, and economic health problems in all countries of the world. The incidence of diabetes mellitus in the world doubles every 10–15 years, acquiring the character of a non-infectious epidemic. Therefore, it is extremely important to search for new drugs that help normalize glycemia, prevent complications of diabetes mellitus, and improve the quality of life of patients. These drugs include “Neo inulin”, which has a hypoglycemic, antioxidant, hepatoprotective and angioprotective effect.The aim: to evaluate the effectiveness of “Neo inulin” in the complex treatment of patients with type 2 diabetes mellitus.Materials and methods. The study involved 18 women (average age – 64.5 ± 8.7 years, average weight – 77.8 ± 11.4 kg) and 3 men (average age – 54.6 ± 12.4 years, average weight – 114 ± 40.2 kg). The average duration of type 2 diabetes was 11.0 (7.0–12.0) years. “Neo inulin” was prescribed as 2 capsules per day for 12 weeks in the complex of basic diabetes therapy To assess the effectiveness of therapy, a study of the quality of life related to health, a biochemical blood test (glycated hemoglobin), a clinical minimum (CBC, OAM, ECG, blood glucose) was carried out, the functional characteristics of tissue blood flow were investigated, and the ankle-brachial index (ABI) was determined. Statistical processing of the results was carried out using the Statistica 6.0 software package (StatSoft Inc., USA). Differences were considered statistically significant at p < 0.05.Results. Statistically significant differences were revealed in the values of all scales of health-related quality of life in patients in the groups before and after treatment with “Neo Inulin”, including the total physical and mental components. An improvement in the functioning of microcirculatory regulation mechanisms was noted, which is confirmed by a statistically significant increase in ABI (1.0 and 0.8 on the right; 0.9 and 0.8 on the left, respectively; p < 0.05) and the coefficient of microcirculation variation (9.2 and 8.3, respectively; p < 0.05). In 57,1 % of cases (12 people), the level of glycated hemoglobin was normalized.Conclusion. The use of a treatment regimen that includes “Neo Inulin” improves the effectiveness of treatment and improves the quality of life of patients with type 2 diabetes mellitus.